Risk assessment, surveillance, and nonpharmaceutical prevention of acute radiation dermatitis: results of a multicentric survey among the German-speaking radiation oncology community: original article - Layer, Katharina; Layer, Julian; Glasmacher, Andrea R.; Sarria, Gustavo R.; Böhner, Alexander M. C.; Layer, Yonah L.; Dejonckheere, Cas S.; Garbe, Stephan; Feyer, Petra; Baumert, Brigitta G.; Schendera, Anke; Baumann, René; et al. (Strahlentherapie und Onkologie, 2023)
Radiation dermatitis (RD) represents one of the most frequent side effects in radiotherapy (RT). Despite technical progress, mild and moderate RD still affects major subsets of patients and identification and management of patients with a high risk of severe RD is essential. We sought to characterize surveillance and nonpharmaceutical preventive management of RD in German-speaking hospitals and private centers.
Online veröffentlicht: 26. April 2023
Gesehen am 17.07.2024